SCN1A and Susceptibility to MTL Epilepsy, Hippocampal Sclerosis and Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the Department of Clinical and Experimental Epilepsy, Institute of Neurology, Queen Square, London, and other centers in the UK and Europe conducted a genome-wide association study in 1018 people with mesial temporal lobe epilepsy (MTLE) with hippocampal sclerosis and 7552 control subjects, with (n=757) and without (n=803) a history of febrile seizures.